Devising a method for the interactive arrangement of structural elements of men’s jacket models - Slavinska, Alla; Matiukh, Serhii; Mytsa, Viktoriia; Syrotenko, Oksana; Dombrovska, Oksana (Eastern-European Journal of Enterprise Technologies, 2022)
This paper has established that one of the directions to correct a designer’s idea is the close relationship between the metric characteristics of a model and the dynamics of updating the shape structure. The need to convolute information about model varieties of a men’s jacket is due to the cyclical nature of fashion. Regression analysis of this study’s results has confirmed the impact of the accumulation of quantitative changes in style attributes on the transition to qualitative changes in shape over 15 years. The periodic repeatability of the five-seam design of a men’s jacket as a typical representative indicates the possibility of using clusters of standard elements. Correlation analysis of the update of mobile attributes (an increase along the waistline and the lapel width) confirms a high level of connection with the silhouette characteristic. Information and analytical material for encoding classification features of the functional components of model designs for an industrial product range collection has been formed. A variant for convoluting the sets of classification features in the process of sampling sorting relative to the basic list of functional nodes has been proposed. The 24×24 compatibility matrix built makes it possible to apply the morphological box method to compare sample sets. The presence of uniformity of the average value of accumulated frequencies Kc.u.=0.72, Kt.u.=0.69 confirms the membership of the sample in the typological series. Having a common encoding system simplifies the selection of models from the internet-based product range collections. The method of sorting the models-proposals of the resulting layout set has been confirmed by the validity coefficient Kv=0.71, which makes it possible to verify the perception of a jacket design as a typical representative of modern structure. Practical recommendations have been compiled on grouping the records of industrial product range collection model codes into industrial series, which enable control over the launch of articles within the manufacturing process.